Gut microbiota-derived metabolites in inflammatory diseases based on targeted metabolomics - Xu, Hui; Pan, Li-Bin; Yu, Hang; Han, Pei; Fu, Jie; Zhang, Zheng-Wei; Hu, Jia-Chun; Yang, Xin-Yu; Keranmu, Adili; Zhang, Hao-Jian; Bu, Meng-Meng; Jiang, Jian-Dong; et al. (Frontiers in Pharmacology, 2022)
The gut microbiota plays an important role in inflammatory diseases. Metabolites in the three metabolic pathways of tryptophan (Trp), histidine (His), and phenylalanine (Phe) can affect various inflammatory conditions, such as obesity, diabetes, arthritis, colitis, atherosclerosis, and neuroinflammation. We established an LC–MS/MS method to measure 17 metabolites—Trp, 3-indole-acetic acid (Iaa), 3-indole-lactate (Ila), 3-indole-propionic acid (Ipa), 3-indole formaldehyde (Iald), kynurenine (Kn), kynurenic acid (Kyna), 3-Hydroxyanthranilic acid (3-Haa), His, 3-methylhistidine (3-Mhis), histamine (Hist), imidazole propionic acid (Imp), 4-imidazoacetic acid (Imaa), urocanic acid (Ua), Phe, phenylethylamine (Pea), and hippuric acid (Ha)—in the three metabolic pathways. The method exhibited high sensitivity and good selectivity, linearity, accuracy, precision, stability; and recovery rate; all met the requirements of biological sample analysis. By establishing a rheumatoid arthritis (RA) model of Sprague–Dawley rats and performing 16S rRNA sequencing on their feces, it was found that there was dysbiosis, including changes in phylum level, genus level, and α biodiversity of gut bacteria. The contents of the microbiota metabolites Iaa and Ipa in the model group were significantly decreased, and those of Iald, Kn, Kyna, Ha, and Imp were significantly increased. The common therapeutic drugs Tripterygium glycosides, total glucosides of peony, and their main active ingredients were screened by in vitro incubation with gut bacteria: it was found that Tripterygium glycosides and their active ingredients could lead to a variation in metabolites in the Trp and Phe pathways. Total glucosides and active components of peony could lead to a variation in metabolites in the Phe pathway of the gut microbiota.